Anesthetic Challenges In A Child With A Metallic Spring In The Left Main Stem Bronchus: A Case Report (International Journal of Environmental Sciences, 2025)
Background: Foreign body aspiration (FBA) in children can lead to delayed diagnosis and serious airway complications, particularly when the aspiration event is unwitnessed. We report a case of a 4-year-old male with a chronically retained metallic spring in the left mainstem bronchus, managed successfully with rigid bronchoscopy under general anesthesia.Case presentation: The child had persistent cough and fever for 2 months after an unwitnessed aspiration. Imaging revealed a metallic spring lodged in the left mainstem bronchus with surrounding granulation tissue. Rigid bronchoscopy under general anesthesia with spontaneous ventilation was planned. After retrieval, the child had an episode of bronchospasm, which was promptly managed, and the airway was secured with an endotracheal tube to prevent postoperative complications. The child was monitored in the Pediatric Intensive Care Unit (PICU) and extubated the following day without further complications.Conclusion: This case highlights the importance of high suspicion for FBA in children with persistent respiratory symptoms, the role of rigid bronchoscopy as the gold standard for complex airway foreign bodies, and the need for a dynamic anesthetic strategy with planned postoperative critical care in high-risk airway cases.